Etika pemanfaatan lingkungan hidup dan sumber daya alam dalam perspektif Islam - Trijayanti, Elisna (Maliki Interdisciplinary Journal, 2024)
In order to support human life on this earth and ensure that natural resources can coexist sustainably and mutually beneficially between nature and humans as users and natural resources, the ethics of sustainable utilization of natural resources and the environment seeks to create nature wisely and wisely without destroying the surrounding nature. The purpose of this study is to determine the significance of the ethics of environmental utilization for the environment and the extent of the alignment of Islamic natural resource management ethics with environmental ethics. It is expected that the findings of this research can eventually be applied to how humans utilize the environment and natural resources. Methods This research was conducted using a literature review and a summary of other research projects, this research was conducted as a descriptive investigation. The results showed the need for sustainable development through ethical use of natural resources and the environment. Islam also obliges humans to protect and preserve nature for the benefit of all people. Several principles are necessary for the ethical use of natural resources and the environment, including responsibility, respect for nature, solidarity, compassion, and balance with nature.